Interplay between Inflammation and Stemness in Cancer Cells: The Role of Toll-Like Receptor Signaling - Da-Wei Yeh; Li-Rung Huang; Ya-Wen Chen; Chi-Ying F. Huang; Tsung-Hsien Chuang (Journal of Immunology Research)
Cancer stem cells (CSCs) are a small population of cancer cells that exhibit stemness. These cells contribute to cancer metastasis, treatment resistance, and relapse following therapy; therefore, they may cause malignancy and reduce the success of cancer treatment. Nuclear factor kappa B- (NF-κB-) mediated inflammatory responses increase stemness in cancer cells, and CSCs constitutively exhibit higher NF-κB activation, which in turn increases their stemness. These opposite effects form a positive feedback loop that further amplifies inflammation and stemness in cancer cells, thereby expanding CSC populations in the tumor. Toll-like receptors (TLRs) activate NF-κB-mediated inflammatory responses when stimulated by carcinogenic microbes and endogenous molecules released from cells killed during cancer treatment. NF-κB activation by extrinsic TLR ligands increases stemness in cancer cells. Moreover, it was recently shown that increased NF-κB activity and inflammatory responses in CSCs may be caused by altered TLR signaling during the enrichment of stemness in cancer cells. Thus, the activation of TLR signaling by extrinsic and intrinsic factors drives a positive interplay between inflammation and stemness in cancer cells.